Two classes of optimal LRCs with information (r, t)-locality - Tan, Pan; Zhou, Zhengchun; Sidorenko, Vladimir; Parampalli, Udaya (Designs, codes, and cryptography, 2020)
Locally repairable codes (LRCs) with ( r , t )-locality have received considerable attention in recent years, since they are able to solve common problems in distributed storage systems such as repairing multiple node failures and managing hot data. Constructing LRCs with excellent parameters becomes an interesting research subject in distributed storage systems and coding theory. In this paper, we present two constructions of LRCs with information ( r , t )-locality based on linear algebra and partial geometry, respectively. Both constructions generate LRCs with new parameters which are optimal with respect to the bound proposed by Rawat et al. (IEEE Trans Inf Theory 62(8):4481–4493, 2016).